MoCA Test: Validation of a five‐minute telephone version - Nasreddine, Ziad S (Alzheimer's & dementia, 2021)
Importance This study validates the use of a telephone version of the MoCA Test, which helps health professionals assess patients remotely. Objectives This is a validation study for a 5 minute telephone version of the MoCA. Study design The subjects’ performances were compared to results obtained from the full version of the MoCA test, at an average of 50.8 days, prior to having completed the 5 Min Telephone MoCA. Participants 84 consecutive subjects were approached to participate in the study. Subjects had to be over 50, male or female, an education level of 6 years. Settings Subjects were recruited in a memory clinic setting. Outcomes and Measures Correct classification and correlation between the Telephone MoCA and full MoCA was evaluated, with area under the curve (AUC) analysis, and Pearson Coefficient respectively. Results 81 subjects were recruited, and 3 subjects declined participation. The average age of the subjects was 69 (Range 47‐92) with a sex distribution of 42 females and 41 males. The average education level for the subjects was 12.6 years. The 5 Min Telephone MoCA results correlated well with the full version of the MoCA, with an area under the curve of 0.864 and a strong Pearson Coefficient of 0.74. Conclusion and Relevance The 5 Min Telephone MoCA is feasible, practical, and reliable, when compared to the full, in‐clinic, MoCA. Clinicians are already familiar with the use of the full MoCA Test, and this new 5 min telephone version, can help them reliably assess patients who cannot make to an in clinic evaluation.